Relationship between age and the impact of revascularization on mortality in patients with non-ST-elevation myocardial infarction. (25th November 2020) - Asano, T; Mitsuhashi, Y; Yamashita, J; Ito, R; Saji, M; Wakabayashi, K; Yahagi, K; Shinke, T; Mase, T; Miyachi, H; Higuchi, S; Miyauchi, K; et al.
Abstract: Background: It is known that the early coronary revascularization in patients with non-ST-elevation myocardial infarction (NSTEMI) was associated with favorable clinical outcomes. However, it is still unclear whether this efficacy is equivalent over all the ages of the patients. Methods: Patients with NSTEMI were screened from the database of the Tokyo CCU network registry. Of those, the patients treated without revascularization (medical treatment) were matched with the patients receiving revascularization by propensity score matching. The probabilities of in-hospital death were calculated in the logistic regression model. In two subgroups stratified according to median of the age (elderly and non-elderly subgroups), the odds ratios of revascularization for in-hospital death were calculated. Results: In the patients registered between 2013 and 2017, 4, 851 patients with NSTEMI were identified. After the screening, 370 patients with medical treatment were matched with 370 patients treated with revascularization. The incidence of in-hospital death was significantly higher in the patients with medical treatment (20.3% vs 13.0%, P=0.01). The two probability curves of in-hospital death in patients with and without revascularization converged as age increased. In the elderly subgroup, the revascularization was not significantly associated with favorable outcome of mortality, whereas it had a significant impact on mortality in the non-elderly subgroup (odds ratio: 0.47 [95% CI 0.23–0.95]). Conclusion: The impact of revascularization on short-term mortality in patients with NSTEMI tended to be reduced as age increased. Funding Acknowledgement: Type of funding source: None